Kakilingan Sambal Texts with Grammatical Analysis - Yamashita, Michiko (The Archive, 2025)
This thesis presents a comprehensive description of the basic phonological and syntactic structures of a dialect of the Sambal language which is spoken in the sitio of Kakilingan, barrio Sta. Fe, municipality of San Marcelino, province of Zambales. The term “Kakilingan Sambal” is used to refer to this dialect which is also used in the neighboring areas of Kakilingan… … Linguistically, Kakilingan Sambal is very close to Botolan Sambal. The differences between these two dialects consist mainly of some phonological features and a few lexical items. 1 Other known dialects of Sambal are Iba Sambal, Sta. Cruz Sambal and Bolinao. 2 None of these dialects is as close to Kakilingan Sambal as Botolan Sambal is. The analysis of Kakilingan Sambal presented in this thesis is based on texts consisting of 21 stories told to me by Aytas between April 1977 and April 1979 in Kakilingan. I recorded the stories on a taperecorder and transcribed and translated them with the help of an Ayta girl 3 who knew, besides her native dialect, Tagalog and Ilokano. I compared the language used in the texts with the language the Aytas used in ordinary conversation and did not find any difference between the two. Thus, in the thesis, whenever I needed forms which are not supplied by the texts, I did not hesitate to elicit them directly from informants.